2015
DOI: 10.3168/jds.2014-8659
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diets containing grape seed, linseed, or both on milk production traits, liver and kidney activities, and immunity of lactating dairy ewes

Abstract: This study aimed to evaluate the effects of the dietary inclusion of grape seed, alone or in combination with linseed, on milk production traits, immune response, and liver and kidney metabolic activity of lactating ewes. Twenty-four Sarda dairy ewes were randomly assigned to 4 dietary treatments consisting of a control diet (CON), a diet containing 300 g/d per head of grape seed (GS), a diet containing 220 g/d per head of extruded linseed (LIN), and a diet containing a mix of 300 g/d per head of grape seed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
36
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 50 publications
10
36
2
Order By: Relevance
“…The inclusion of DGP in cows' diet did not influence milk yield, according Nielsen and Hansen who noted only a slight tendency towards increased milk yield although non‐significant . In agreement with other studies, DGP did not modify the chemical composition of milk obtained from the GP+ group . However, other studies reported a reduction in the content of urea in the milk of cows that received a ration integrated with GP or by‐products of the oenological industry or reduction in the protein content as a resulting effect of polyphenols action …”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The inclusion of DGP in cows' diet did not influence milk yield, according Nielsen and Hansen who noted only a slight tendency towards increased milk yield although non‐significant . In agreement with other studies, DGP did not modify the chemical composition of milk obtained from the GP+ group . However, other studies reported a reduction in the content of urea in the milk of cows that received a ration integrated with GP or by‐products of the oenological industry or reduction in the protein content as a resulting effect of polyphenols action …”
Section: Discussionsupporting
confidence: 82%
“…11 Nudda et al evaluated the effect of dietary inclusion of grape seed flour in sheep, in combination or not with linseed, on milk production, on hepatic and renal metabolism and on the immune status of animals. 12 Recently was also analysed the whole-transcriptome of Friesian calves fed with a GP-supplemented diet, observing variations in the pathway of cholesterol lipid biosynthesis, and this effect was consistent with a reduction in both serum cholesterol and lipid oxidation in the carcasses. 13 In addition to nutritional parameters, Torri et al explored the sensory properties of cow milk cheeses fortified with grape skin powders, however finding a lower degree of acceptance by consumers than expected.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…The observed inhibition of ER stress and the parallel increase of milk yield by GSGME [13] is noteworthy regarding the relatively low amount of GSGME fed to the cows (1% of DM in the TMR). Other studies dealing with the effect of grape products in ruminants (cows or ewes) used markedly higher concentrations, such as 5 kg dried GM per cow and day [71], 10% grape residue silage of feed DM [72], and 300 g GS per ewe and day [73]. Despite the feeding of much higher amounts of grape products in these studies, only one study observed a slight improvement of milk yield compared to the control group [71].…”
Section: Discussionmentioning
confidence: 99%